Determinan debt behavior pengguna platform peer-to-peer lending - Steven, Steven; Linawati, Nanik (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to examine the effect of financial literacy and financial behavior on debt behavior using a peer-to-peer lending platform. An associative-quantitative research design will be used in this investigation. This study used an online questionnaire, which was distributed to 100 respondents from MSME owners in the garment industry who have used or are currently using a peer-to-peer lending platform with a maximum turnover of 50 billion per year. The research data were analyzed using a structural equation model approach with the PLS (partial least squares) method. The results of this study indicate that financial literacy and financial behavior have a significant effect on debt behavior when using a peer-to-peer lending platform. Therefore, MSME owners need to understand the characteristics and funding through appropriate peer-to-peer lending according to their needs. Meanwhile, the manager of the peer-to-peer lending platform can consider the factors that affect performance and the need to continuously improve the performance of the peer-to-peer lending platform.